SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEBSITE MENERAPKAN METODE PROMETHEE UNTUK MENGHASILKAN DAFTAR URUT KEPEGAWAIAN (STUDI KASUS: DINAS PERIKANAN KOTA PALANGKA RAYA) - Widiatry Widiatry (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
In this Information System of Personnel applied the method of Promethee (The PreferenceRanking Organization Method for Enrichment of Evaluations), which is one method of determining theorder or priority in MCDM (Multi Criterion Decision Making). The application of this method is usedto generate a Ranking List of Departures, with successive criteria of rank, position, occupationaltraining, education, employment and Age. In developing the Human Resources Information Systembased on the website used Waterfall software development method according to Ian Sommerville in2011 with stages, requirements definition, system and software design, implementation and unit testing,integration and system setting and operation and maintenance. The software used in building thiswebsite is Netbeans, SQLyog and XAMPP. This Information System can run well as has been doneblackbox testing on this information system. Staffing Information System Fisheries Department ofPalangka Raya City based website is built with the hope of the optimization of work and servicefunctions, so it can facilitate the processing of employee data in order to produce relevant information.